Community Economic Empowerment as a Stunting Prevention Program in Seulalah Baru Village - Ziauddin, Zulfa Eliza; Zuliani, Rafiza; Agustinar, Agustinar (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Stunting is a chronic nutritional problem characterized by a child's height being below the standard for their age. Stunting can cause various health problems, including cognitive, motor and social emotional development disorders. Seulalah Baru Village is one of the villages in Langsa City that has a high prevalence of stunting. One of the factors causing stunting in this village is poverty. Community economic empowerment is one strategy that can be used to prevent stunting. Community economic empowerment can increase community income, so that people can fulfill their nutritional needs optimally. This research aims to examine the effectiveness of community economic empowerment as a stunting prevention program in Seulalah Baru Village. This research uses quantitative research methods with a quasi-experimental research design. The research results show that community economic empowerment can reduce the prevalence of stunting in Seulalah Baru Village. This is shown by the results of the t test which shows a significant difference between the prevalence of stunting in the intervention group and the control group. Based on the results of this research, it can be concluded that community economic empowerment is an effective program to prevent stunting.